Implementing and evaluating far‐field 3D X‐ray diffraction at the I12 JEEP beamline, Diamond Light Source. (16th May 2022) - Ball, James A. D.; Kareer, Anna; Magdysyuk, Oxana V.; Michalik, Stefan; Vrettou, Anastasia; Parkes, Neal; Connolley, Thomas; Collins, David M.
Abstract : Three‐dimensional X‐ray diffraction (3DXRD) has been implemented and demonstrated to be feasible at the I12 JEEP beamline using a single‐phase ferritic steel sample. Measurements and associated accuracies of position, orientation and strain state of around 2000 grains were determined. These were obtained from a customized data acquisition and analysis pipeline based on the FABLE software package. Abstract : Three‐dimensional X‐ray diffraction (3DXRD) is shown to be feasible at the I12 Joint Engineering, Environmental and Processing (JEEP) beamline of Diamond Light Source. As a demonstration, a microstructually simple low‐carbon ferritic steel was studied in a highly textured and annealed state. A processing pipeline suited to this beamline was created, using software already established in the 3DXRD user community, enabling grain centre‐of‐mass positions, orientations and strain tensor elements to be determined. Orientations, with texture measurements independently validated from electron backscatter diffraction (EBSD) data, possessed a ∼0.1° uncertainty, comparable with other 3DXRD instruments. The spatial resolution was limited by the far‐field detector pixel size; the average of the grain centre of mass position errors was determined as ±∼80 µm. An average per‐grain error of ∼1 × 10 −3 for the elastic strains was also measured; this could be reduced in future experiments by improving sample preparation, geometry calibration, data collection and analysis techniques. Application of 3DXRD onto I12 shows great potential, where its implementation is highly desirable due to the flexible, open architecture of the beamline. User‐owned or designed sample environments can be used, thus 3DXRD could be applied to previously unexplored scientific areas.